2019
DOI: 10.1148/rycan.2019194003
|View full text |Cite
|
Sign up to set email alerts
|

68Ga FAPI PET/CT: Tracer Uptake in 28 Different Kinds of Cancer

Abstract: F luorodeoxyglucose (FDG) PET/CT is the primary imaging modality for cancer diagnosis, staging, and management. However, in cancers with high background uptake, inflammation, or low metabolic activity, FDG uptake is not as effective at tumor delineation and identifying metastatic lesions. An attractive complementary imaging target is the fibroblast-activated protein (FAP), which is preferentially expressed in cancer-associated fibroblasts. FAP overexpression is linked to increased local inflammation, suppressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(40 citation statements)
references
References 1 publication
3
37
0
Order By: Relevance
“…Follow-up laboratory examinations showed that the serum alpha-fetoprotein (AFP) level increased progressively to 71.5 ug/L (reference range: 0-3 ug/L). 18 F-FDG PET/ CT and 18 F-FAPI PET/CT were performed to further evaluate the nature of the lesion (Figure 1). 18 F-FDG PET/CT revealed multiple iso-metabolic metastases in the right mesh membrane, hypo-metabolic tumor necrosis after RFA in the right liver, and low uptake in peritoneal metastases (Figure 1A).…”
Section: Case Presentationmentioning
confidence: 99%
See 3 more Smart Citations
“…Follow-up laboratory examinations showed that the serum alpha-fetoprotein (AFP) level increased progressively to 71.5 ug/L (reference range: 0-3 ug/L). 18 F-FDG PET/ CT and 18 F-FAPI PET/CT were performed to further evaluate the nature of the lesion (Figure 1). 18 F-FDG PET/CT revealed multiple iso-metabolic metastases in the right mesh membrane, hypo-metabolic tumor necrosis after RFA in the right liver, and low uptake in peritoneal metastases (Figure 1A).…”
Section: Case Presentationmentioning
confidence: 99%
“…Integrated 18 F-FDG PET/CT has emerged as an important tool for diagnosis, staging, restaging and treatment monitoring for patients with various different types of tumors because it provides functional and morphological information in a single and noninvasive examination. 1 However, it has some limitations in the diagnosis of HCC and detecting recurrent lesions during follow-up, with little change in treatment resulting.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…At present, PET/CT is a commonly used imaging method for the preoperative systemic evaluation and staging of malignant tumors and the glucose analog, fluorodeoxyglucose (FDG) is the most commonly used radioactive tracer for detecting malignant tumors on PET/CT (9)(10)(11)(12)(13)(14). However, FDG has weak efficacy for tumor delineation and the identification of metastatic lesions (15,16,17), making it difficult to distinguish between inflammation and malignancy on FDG PET/CT (7,(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%